2019
DOI: 10.1016/j.heliyon.2019.e01493
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and structured biodiversity in a diverse set of wild cranberry clones

Abstract: Wild germplasm with elevated antioxidants are a useful resource for using directly and in a breeding program. In a study with 136 wild clones and two cranberry cultivars, phenolic, flavonoid and anthocyanin contents varied 2.79, 2.70 and 17.46 times, respectively. The antioxidant activity ranged from 1.17 ± 0.01 to 2.53 ± 0.05 mg/g and varied 2.16 times. Seventy-five of wild clones and the cultivar Franklin were grouped into five distinct classes by molecular structure analysis using inter simple sequence repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…In their study, Debnath and Sion [ 80 ] reported no correlation between genetic diversity based on ISSR markers and chemical diversity based on antioxidant activity and anthocyanin content in lingonberry. Similar observations were also reported in strawberry [ 81 ] and cranberry using ISSR, EST–SSR, and EST–PCR markers [ 82 ]. We also studied the association of EST–SSR, G–SSR and EST–PCR markers with 70 genotypes of blueberry and found that only one marker was associated with TPC, as revealed by DPPH assay, and five markers were associated with both TPC and TFC.…”
Section: Discussionsupporting
confidence: 87%
“…In their study, Debnath and Sion [ 80 ] reported no correlation between genetic diversity based on ISSR markers and chemical diversity based on antioxidant activity and anthocyanin content in lingonberry. Similar observations were also reported in strawberry [ 81 ] and cranberry using ISSR, EST–SSR, and EST–PCR markers [ 82 ]. We also studied the association of EST–SSR, G–SSR and EST–PCR markers with 70 genotypes of blueberry and found that only one marker was associated with TPC, as revealed by DPPH assay, and five markers were associated with both TPC and TFC.…”
Section: Discussionsupporting
confidence: 87%
“…The content of total anthocyanins ranged from 695 to 1716 mg/100 g dm for the six cultivars of Vaccinium macrocarpon L. grown in Poland [ 12 ]. Of one hundred and thirty-six wild cranberry fruits, Vacciniun macrocarpon Aiton, and two cultivars, ‘Franklin’ and ‘Bergman’, Debnath and An [ 22 ] observed the total anthocyanins content for all cranberry genotypes to differ significantly ( p < 0.05). Variation ranged from the least amount of total anthocyanins in the wild clone cranberry NL77 of 0.13 mg/g fw to the highest amount detected in the genotype ‘Franklin’ of 2.27 mg/g fw [ 22 ].…”
Section: Chemical Constituents Of Cranberry Fruitmentioning
confidence: 99%
“…Of one hundred and thirty-six wild cranberry fruits, Vacciniun macrocarpon Aiton, and two cultivars, ‘Franklin’ and ‘Bergman’, Debnath and An [ 22 ] observed the total anthocyanins content for all cranberry genotypes to differ significantly ( p < 0.05). Variation ranged from the least amount of total anthocyanins in the wild clone cranberry NL77 of 0.13 mg/g fw to the highest amount detected in the genotype ‘Franklin’ of 2.27 mg/g fw [ 22 ]. In another study by Česonienė et al [ 15 ], six anthocyanins were identified in the two species of cranberries, Vaccinium macrocarpon and Vaccinium oxycoccos .…”
Section: Chemical Constituents Of Cranberry Fruitmentioning
confidence: 99%
See 2 more Smart Citations